Canadian emergency physician psychological distress and burnout during the first 10 weeks of COVID‐19: A mixed‐methods study - Kerstin de Wit; Mathew Mercuri; Clare Wallner; Natasha Clayton; Patrick Archambault; Kerri Ritchie; Caroline Gérin‐Lajoie; Sara Gray; Lisa Schwartz; Teresa Chan; for the Network of Canadian Emergency Researchers (Journal of the American College of Emergency Physicians Open)
Abstract Objectives The aim of this study was to report burnout time trends and describe the psychological effects of working as a Canadian emergency physician during the first weeks of the coronavirus disease 2019 (COVID‐19) pandemic. Methods This was a mixed‐methods study. Emergency physicians completed a weekly online survey. The primary outcome was physician burnout as measured by the emotional exhaustion and depersonalization items, from the Maslach Burnout Inventory. We captured data on work patterns, aerosolizing procedures, testing and diagnosis of COVID‐19. Each week participants entered free text explaining their experiences and well‐being. Results There were 468 participants who worked in 143 Canadian hospitals. Burnout levels did not significantly change over time (emotional exhaustion P = 0.632, depersonalization P = 0.155). Three participants were diagnosed with COVID‐19. Being tested for COVID‐19 (odds ratio [OR] 11.5, 95% confidence interval [CI] 3.1–42.5) and the number of shifts worked (OR 1.3, 95% CI 1.1–1.5 per additional shift) were associated with high emotional exhaustion. Having been tested for COVID‐19 (OR 4.3, 95% CI 1.1–17.8) was also associated with high depersonalization. Personal safety, academic and educational work, personal protective equipment, the workforce, patient volumes, work patterns, and work environment had an impact on physician well‐being. A new financial reality and contrasting negative and positive experiences affected participants’ psychological health. Conclusion Emergency physician burnout levels remained stable during the initial 10 weeks of this pandemic. The impact of COVID‐19 on the work environment and personal perceptions and fears about the impact on lifestyle have affected physician well‐being.